Dynamic characteristics analysis of a once-through heat recovery steam generator. (5th June 2020) - Du, Wenjing; Li, Jinbo; Yuan, Baoqiang
Highlights: A mathematic model for HRSG is established for dynamic characteristic analysis. Genetic algorithm is applied to adjust the operational parameters of the HRSG. The start-up and off-design operation conditions of the HRSG are simulated. A delay appears in the response of feed water to the disturbance of flue gas. HRSG saturation state depends on combined effect of feed water and flue gas. Abstract: A U-type once-through heat recovery steam generator (HRSG) is investigated in this paper and emphasis is laid on a mathematical model for its dynamic characteristics analysis. The model is built in the Matlab/Simulink environment based on the thermodynamics principles and conservations of mass, momentum, and energy. Genetic algorithm (GA) is applied as a parameter identification technique to adjust the model parameters. Real-time on-site measurement data of start-up and off-design operation for different conditions are used for model testing and validation. The model can be used to represent the real export parameter changes of heating surfaces for different operating conditions. The results show good predictive capabilities at the respective operating points and the corresponding RMSE (root mean square errors) ranges from 2.9659 to 4.4292, which shows a high accuracy. Simulation results on the outlet temperatures and steam production of single-phase and two-phase heating surfaces are presented. The process of phase transformation is also clearly simulated. The heat preservation coefficient and operational parameters of dynamic characteristics is favorable for the HRSG design optimization and performance prediction.